Penggunaan model pembelajaran think pair share dengan media gambar seri untuk meningkatkan keterampilan menulis karangan narasi kelas III sekolah dasar - Retno Riana Sari; Muhammad Ismail Sriyanto; Joko Daryanto (Universitas Sebelas Maret, 2019)
Abstract. The purpose of this research is to improve the narrative essay writting skills for third grade students of SD N Sayangan No. 244 Surakarta 2018/2019 academic year through the use of Think Pair Share learning model with picture series. This type of research is classroom Action Research conducted in 2 cycles. The subject of this research consisted of teacher and class III students with a total 30 students with 13 men and 17 women. The data obtained in this study were collected by interview, observation,test, and documentation techniques. The technique used in testing the validity of this research data is content validity and triangulation. The analysis tecnique used is interactive analysis techniques. The result of this study indicate that There was an increase in every aspect of narrative essay writing skills, namely aspects of content, organization, vocabulary, language development, and mechanics. And then the classical completeness of students in narative essay writting skills on pre-action activities was 16,67%. Then it increased to 63,33% in the frist cycle and increased to 86,67% in the second cycle. Based on the result of the research data it can be concluded that the use of Think Pair Share learning models with picture series can improve the narrative essay writing skills of class III SD N Sayangan No. 244 Surakarta academic year 2018/2019.Keyword: Think Pair Share learning model, picture series, narrative essay writing skill, elementary school